Image-proven thromboembolism in patients with severe COVID-19 in a tertiary critical care unit in the United Kingdom. Issue 193 (September 2020) - Desborough, Michael J.R.; Doyle, Andrew J.; Griffiths, Alexandra; Retter, Andrew; Breen, Karen A.; Hunt, Beverley J.
Highlights: Venous thrombosis is common in patients with severe COVID-19 pneumonia. Many of these thromboses may be immunothromboses due to local inflammation, rather than thromboembolic disease. Anticoagulated patients with COVID-19 pneumonia have a risk of major bleeding.